The impact of different standards of opponents on observed player performance in the English Premier League - Redwood-Brown, A.; Bussell, C.; Bharaj, H. S. (Journal of Human Sport & Exercise, 2012)
The purpose of the investigation was to develop an understanding of how the performance of a soccer team is affected when playing against different standards of opponents in the English Premier League. Twenty-nine Premier League matches were analysed during the 2010-2011 season for 18 selected performance indicators. Standards of opposing teams were defined as being top, middle or bottom depending on their final league position. The participating team was categorised in the `middle` category and eighteen players from the squad were selected to take part in the study. Comparisons (mean±SD) were made between the team`s performances on selected performance indicators against teams ranked as top, middle and bottom. A one-way ANOVA analysed the team`s performance behaviour along with: five positional units (centre-back, full-back, centre midfield, wide midfield, centre forward); and individual player performance behaviour. At team level, successful passes (?=0.047) were significantly higher against middle (84.2%) compared with top (83.8%) and bottom standard teams (83.3%). Interceptions (?=0.016) were also significantly higher against middle (11.2±8.3) when compared with playing against top standard teams (8.4±5.2). The findings suggested the team generally performed better against middle than top or bottom standard opponents. Possession/passing was highlighted as a key factor influencing the performance at team level, although no account for game state was considered. The findings suggest that differences in individual player performance are not always evident at team or unit level which previous research has failed to address. The current study has shown that player, unit and team performance changes as a function of opposition standard but must be considered in the future in relation to game state.